THE UTILIZATION OF BUNGO RAYO LEAF PLANT AS TRADITIONAL MEDICINE IN NEWLAK VILLAGE, TANJUNG NEW REGENCY, TANAH DATAR - Dhiyaa Afdila (Department of Science Education, 2022)
This paper aims to describe the benefits of traditional medicinal plants and how to use them by the community and their suitability as a medium of information for the community in Desa Barulak Kec. Tanjung Baru Kab. Tanah Datar. This research is a descriptive research with interview method with data collection using roaming and observation techniques.In genaral, the plaint height is about 2 to 5 meters. The leaves are broad ovoid. The part that is used is the leaves. Usually used by squezzed water then drunk.**Abstact is written into two languages (English and Bahasa Indonesia)!